Therapeutic effects of Ventolin versus hypertonic saline 3% for acute bronchiolitis in children - Zamani, Mohammad-Ali (Med J Islam Repub Iran, 2015)
Background: Complications of Ventolin as the most common drug used for bronchiolitis are widely known. The present study was conducted to determine the efficacy of hypertonic saline 3%, compared with Ventolin, for treatment of acute bronchiolitis in children. Methods: This double-blinded clinical trial study was conducted in Hajar Hospital, Shahrekord, Iran, from 2011 to 2012. A total of 70 patients under the age of two years with bronchiolitis were divided into two groups of 35 each. Ventolin nebulizer and hypertonic saline 3% nebulizer three times per day were administered in the first (Ventolin) and second (Hypersaline) group, respectively. The length of recovery was compared between the two groups. The data were analyzed by SPSS software (version 22) using chi-square, t-test, paired t-test, and Mann-Whitney. Results: The mean±SD length of recovery was 4.14±0.9 and 3.06±0.6 in the Ventolin and hypersaline groups, respectively. The mean duration of recovery was significantly lower in the hypersaline group (p<0.001). Conclusion: Hypertonic saline 3% nebulizer has more pleasant therapeutic effects on acute bronchiolitis than Ventolin. Therefore, use of hypertonic saline 3% nebulizer is recommended for the treatment of acute bronchiolitis in children under two years old.